Color fractal descriptors for adaxial epidermis texture classification - Backes, André R.; de Mesquita Sá Junior, Jarbas Joaci; Kolb, Rosana Marta [UNESP] (Springer Nature, 2015)
The leaves are an important plant organ and source of information for the traditional plant taxonomy. This study proposes a plant classification approach using the adaxial epidermis tissue, a specific cell layer that covers the leaf. To accomplish this task, we apply a high discriminative color texture analysis method based on the Bouligand- Minkowski fractal dimension. In an experimental comparison, the success rate obtained by our proposed approach (96.66%) was the highest among all the methods used, demonstrating that the Bouligand- Minkowski method is very suitable to extract discriminant features from the adaxial epidermis. Thus, this research can significantly contribute with other studies on plant classification by using computer vision.
Keywords: Adaxial epidermis tissue; Bouligand-Minkowski method; Color; Fractal dimension; Texture analysis